The Analisis Penerapan Sistem Informasi Akuntansi Persediaan Obat Dalam Pencegahan Kecurangan Pada Puskesmas Tikala Kota Manado - Kakunsi, Indah Eunike; Tasiam, Ezrani; Rori, Midian Cristy (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the implementation of Accounting Information Systems (AIS) in drug inventory management and their role in preventing fraud at Tikala Public Health Center (Puskesmas Tikala) in Manado City. The research uses a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings indicate that AIS has been applied manually and semi-computerized, especially in the planning, receiving, storage, and distribution of medicines. Although not yet fully integrated digitally, the current system has helped enhance transparency and internal control. AIS plays a role in detecting potential fraud through proper record-keeping and regular monitoring. The main challenges in implementing AIS include limited human resources, inadequate technological infrastructure, and the absence of an official application system from the Health Department. This study recommends the development of an integrated system, regular staff training, and the enhancement of supporting infrastructure to ensure more effective and accountable drug inventory management.